Functional study of the Saccharomyces cerevisiae Nha1p C-terminus - Kinclová, O; Ramos, J; Potier, S; Sychrová, H (Molecular microbiology, 2001)
Saccharomyces cerevisiae cells possess an alkali metal cation antiporter encoded by the NHA1 gene. Nha1p is unique in the family of yeast Na+/H+ antiporters on account of its broad substrate specificity (Na+, Li+, K+) and its long C-terminus (56% of the whole protein). In order to study the role of the C-terminus in Nha1p function, we constructed a series of 13 truncated NHA1 versions ranging from the complete one (2958 nucleotides, 985 amino acids) down to the shortest version (1416 nucleotides, 472 amino acids), with only 41 amino acid residues after the last putative transmembrane domain. Truncated NHA1 versions were expressed in an S. cerevisiae alkali metal cation-sensitive strain (B31; ena1-4Delta nha1Delta). We found that the entire Nha1p C-terminus domain is not necessary for either the proper localization of the antiporter in the plasma membrane or the transport of all four substrates (we identified rubidium as the fourth Nha1p substrate). Partial truncation of the C-terminus of about 70 terminal amino acids improves the tolerance of cells to Na+, Li+ and Rb+ compared with cells expressing the complete Nha1p. The presence of the neighbouring part of the C-terminus (amino acids 883-928), rich in aspartate and glutamate residues, is necessary for the maintenance of maximum Nha1p activity towards sodium and lithium. In the case of potassium, the participation of the long C-terminus in the regulation of intracellular potassium content is demonstrated. We also present evidence that the Nha1p C-terminus is involved in the cell response to sudden changes in environmental osmolarity.
Keywords: Saccharomyces cerevisiae Proteins; Cations, Monovalent; Saccharomyces cerevisiae; membránové proteiny; Membrane Proteins; molekulární sekvence - údaje; Amino Acid Sequence; lithium; Hydrogen-Ion Concentration; sodík; Cation Transport Proteins; Lithium; kationty jednomocné; osmolární koncentrace; koncentrace vodíkových iontů; Intracellular Fluid; Sodium; Cell Membrane; Sodium-Hydrogen Exchangers; substrátová specifita; Substrate Specificity; Osmolar Concentration; buněčná membrána; Saccharomyces cerevisiae - proteiny; sekvence aminokyselin; intracelulární tekutina; Molecular Sequence Data; Na(+)-H(+) antiport; proteiny přenášející kationty